Pengaruh Penggunaan Zat Aditif Minyak Cengkeh Terhadap Prestasi Mesin Sepeda Motor Injeksi 4 Langkah - Paksi, Pegi Satria Eka; Sudia, Budiman; Kadir, Abd . (Enthalpy : Jurnal Ilmiah Mahasiswa Teknik Mesin, 2021)
At this time, fuel oil has become a basic need by the Indonesian people due to the increase in the use of vehicles, while the government is still subsidizing fuel oil. For this reason, it is necessary to save on the use of fuel oil. The alternative that can be done  is  reformulating  fuel  oil  with  additives  that  function  to  enrich  the  oxygen content in the fuel. The purpose of this study is to determine the performance of the engine which can be seen from the fuel consumption and acceleration of the vehicle in which the percentage of clove oil mixing which is most effective in its use will be known. This research includes mixing 1.5%, 2.5%, 3.5% and 4.5% mixture of clove  oil  to  premium/gasoline.  In  this  study,  the  formulation  of  a  premium fuel/gasoline  mixture  with  clove  oil  was  most  effective  and  efficient  on  fuel consumption, namely in the stationary test it was a mixture of 1.5% while in the running test it was a mixture of 2.5%. For the acceleration test, the best mixing formulation is in the 4.5% mixture formulation, both in the 0-70 km and 40-70 km tests.